Optimizing Child Development Given Roscoe Pound's Social Interest Theory (Study at Alif Islamic Daycare) - Alfina, Fitria Tahta; Mukarromah, Fahira Lailatul; Ariany, Nina; Rifqi, Muhammad Jazil (Raudhatul Athfal: Jurnal Pendidikan Islam Anak Usia Dini, 2024)
This study aims to examine how to optimize children's development in the context of the Social Interest Theory promoted by Roscoe Pound, with a focus on studies studied at Alif Islamic Daycare. In the context of daycare institutions, social interaction, and care are the keys to understanding how social factors influence children's development. This research adopts a qualitative approach, in which the data collection method uses interviews, observation, questionnaires, and document analysis to explore the impact of applying social interest theory at Alif Islamic Daycare. The main participants targeted in the research are care staff, parents, and children attending Alif Islamic Daycare. The data is analyzed by referring to the concepts contained in social interest theory such as the influence of the social environment on morality, the balance between individual, public, and social interests in the concept of general security as well as social interests which refer to society's standards for individual life. The research results show that a social interests-oriented approach in managing Alif Islamic Daycare makes a significant contribution to optimizing children's development. Alif Islamic Daycare prioritizes Islamic values so that they can have a positive impact on children's social, emotional, and cognitive development. A supportive, safe, and comfortable environment as well as Islamic norms are a strong foundation for the development of children's personalities at Alif Islamic Daycare